2016
DOI: 10.1096/fj.201600459rr
|View full text |Cite
|
Sign up to set email alerts
|

Rutin ameliorates obesity through brown fat activation

Abstract: Increasing energy expenditure through activation of brown adipose tissue (BAT) is a critical approach to treating obesity and diabetes. In this study, rutin, a natural compound extracted from mulberry and a drug used as a capillary stabilizer clinically for many years without any side effects, regulated whole-body energy metabolism by enhancing BAT activity. Rutin treatment significantly reduced adiposity, increased energy expenditure, and improved glucose homeostasis in both genetically obese (Db/Db) and diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
140
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 50 publications
8
140
0
Order By: Relevance
“…In the present study, guarana activated BAT by promoting mass increase, mitochondrial biogenesis, and UCP1 overexpression, which are important mechanisms of BAT activation (Lidell et al, ; Sanchez‐Delgado et al, ). Corroborating our data, many other extracts/compounds effective in weight management have been shown to activate BAT in humans and animal models (Saito & Yoneshiro, ; Yoneshiro et al, ; Yuan et al, ). BAT activation can be stimulated by other factor like ambient temperature, which is a crucial factor in determining organismal energy balance, at least in part through BAT activation (Lidell et al, ; Sanchez‐Delgado et al, ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, guarana activated BAT by promoting mass increase, mitochondrial biogenesis, and UCP1 overexpression, which are important mechanisms of BAT activation (Lidell et al, ; Sanchez‐Delgado et al, ). Corroborating our data, many other extracts/compounds effective in weight management have been shown to activate BAT in humans and animal models (Saito & Yoneshiro, ; Yoneshiro et al, ; Yuan et al, ). BAT activation can be stimulated by other factor like ambient temperature, which is a crucial factor in determining organismal energy balance, at least in part through BAT activation (Lidell et al, ; Sanchez‐Delgado et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…Currently, many key factors have been widely used to indicate BAT activation, such as BAT expansion, UCP1 content, and mitochondrial numbers (Lidell, Betz, & Enerbäck, 2014;Sanchez-Delgado et al, 2015). It is known that many plants (extracts and phytochemicals) are able to activate the BAT (Saito & Yoneshiro, 2013;Yoneshiro et al, 2017;Yuan et al, 2017). Thus, these plants become an attractive therapeutic targets to treat obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of PGC1‐α plays an important role in mitochondrial biogenesis and SIRT1‐mediated PGC1‐α deacetylation and activation is critical for mitochondrial function in BAT . Several polyphenols from plant extract, such as resveratol and rutin are known to directly stimulate BAT thermogenesis and promote WAT browning by increasing expression and activation of SIRT1 . In this study, we found that C3G treatment could markedly increase mtDNA copy number, PGC1‐α, TFAM , and NRF1/2 expression both in BAT and sWAT (Figs.…”
Section: Discussionmentioning
confidence: 55%
“…However, while supplements at this dose (1320 mg) and higher are readily available in pill or capsule form for general public consumption, we do not advocate their usage. In addition to C3G, there were a number of other bioactive substances (such as resveratrol and rutin) in our daily diet . Therefore, other bioactive compounds in our daily diet may work in concert with single purified C3G to improve the BAT activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation